Managing Acute Wounds with Negative Pressure System in a Developing Country. (12th June 2013) - Akpaloo, J.; Yorke, J.; Agbenorku, P.; Yenli, E. M. T.
Abstract : Introduction . The negative pressure system has been found to be a valuable addition to the various procedures of wound management and has been widely accepted to be safe and effective in promoting wound healing. Aim . The study seeks to find out the outcome of the use of the VAC device in the treatment of patients with acute wounds. Materials and Methods . Between January 2009 and December 2011, a consecutive nonrandomized study was conducted among 48 patients who presented with acute wounds at the Komfo Anokye Teaching Hospital. Patients were made to undergo negative pressure wound therapy using the VAC device. Results . Forty-eight patients with various degrees of acute wounds were treated, of which 43 (89.6%) were females and 5 (10.4%) were males. Ages of patients ranged from 19 to 78 years. Satisfaction with rate of wound healing revealed that 86.7% and 8.9% had excellent and good healing, respectively, while 4.4% said theirs was satisfactory. Therapy was discontinued in three (6.3%) patients who developed some complications. Conclusion . There was reduction in the hospitalization by patients thereby reducing costs. Also, quality of life of persons who had undergone the therapy with the VAC device had improved. Even though a few device-related complications were observed, patient satisfaction was high.